Gender Representation in English Learning Materials Textbook at the Eight Grade of SMP Negeri 3 Sitolu Ori in 2024/2025 - Yarnita Zega; Yaredi Waruwu; Adieli Laoli; Elwin Piarawan Zebua (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Gender is a concept that refers to the roles, behaviors, activities, and attributes deemed appropriate for men and women within a particular culture or society. Gender socialization has traditionally been carried out by spreading messages, discourses, values, norms, beliefs, and models that represent specific gender representations. Textbooks are one of the tools for cultural socialization, including the concept of gender. If textbooks address gender issues without further understanding, it can confuse students. The aim of this research is to analyze how gender is represented in textbooks, the existence of gender representation inequality, and to determine whether the textbook used still contains gender stereotypes or gender bias. This research uses a qualitative method with a content analysis approach. The subject of this study is the English textbook titled Bright an English Course for SMP/MTs Grade VIII, authored by Nur Zaida. Data analysis techniques are based on six aspects from Logsdon’s framework. The results of this study show gender inequality in the analyzed textbook, particularly in the aspect of Patterns of Mentioning Female/Male Names. Female names were mentioned only 3 times, contributing 23% of the total mentions, whereas male names were mentioned 10 times, contributing 77%. Therefore, there is a clear difference in the number of mentions between females and males, with males being much more frequently mentioned. The 54% difference indicates a significant imbalance in gender representation in the context of name mentions.